Trajectories of Infants' Biobehavioral Development: Timing and Rate of A‐Not‐B Performance Gains and EEG Maturation. Issue 3 (17th January 2018) - MacNeill, Leigha A.; Ram, Nilam; Bell, Martha Ann; Fox, Nathan A.; Pérez‐Edgar, Koraly
Abstract : This study examined how timing (i.e., relative maturity) and rate (i.e., how quickly infants attain proficiency) of A‐not‐B performance were related to changes in brain activity from age 6 to 12 months. A‐not‐B performance and resting EEG (electroencephalography) were measured monthly from age 6 to 12 months in 28 infants and were modeled using logistic and linear growth curve models. Infants with faster performance rates reached performance milestones earlier. Infants with faster rates of increase in A‐not‐B performance had lower occipital power at 6 months and greater linear increases in occipital power. The results underscore the importance of considering nonlinear change processes for studying infants' cognitive development as well as how these changes are related to trajectories of EEG power. Abstract : The title for this Special Section isThe Developing Brain: Evidence for Plasticity during Childhood and Adolescence, edited by Amanda E. Guyer, Koraly Pérez‐Edgar, and Eveline A. Crone